Physicochemical and nutraceutical characterization of sirimbache fruit (Gaultheria glomerata (Cav.) Sleumer) (Scientia Agropecuaria, 2017)
The consumption of vegetables with the greatest nutraceutical potential, especially those with high levels of antioxidants such as anthocyanin and phenolic compounds, has become popular among health conscious consumers. The aim of this research was to determine the nutraceutical potential of sirimbache fruits (Gaultheria glomerata (Cav.) Sleumer). Characterization of the berries resulted in the following: 11.4 °Brix, 3.25 pH, 0.35% acidity, 83.74% moisture, 0.16% ash, monomeric anthocyanins (112.88 mg cyanidin 3-glucoside / 100 g of sample), total phenolic compounds (344.37 mg of gallic acid / 100 g of sample) and vitamin C (13.87 mg ascorbic acid/ 100 g of sample). These values indicate that sirimbache is a nutraceutical food of great interest. Therefore, the expansion of sirimbache to health conscious markets may be feasible. Such expansion is of great importance for rural agribusiness, as it could promote the development of new agroindustrial projects in the province of Celendin and other Andean areas of Peru.